Communicating abroad: A case study of Za'atari Syrian refugee camp - Ying Xu; Carleen F. Maitland (International Telecommunications Society (ITS), 2015)
In this study, we examine how refugees in the Middle East stay connected through various communication services. Our findings are based on survey data collected in Za'atari Syrian refugee camp in Jordan. First, we find that social media such as WhatsApp and Facebook are used more frequently compared to mobile voice, SMS, Skype and email. Second, the demographic variables of sex and education level were found to be significant predictors in the choice of communication services in Jordan but have no significant effect in explaining past choices in Syria. In Jordan, men are more likely to use mobile voice, Viber and email, and people with higher education tend to use Viber. These findings provide quantitative evidence of the usage behaviors of refugees, providing valuable information for service providers as well as a basis for future research.
Keywords: 330; Internet; Mobile Phone; Refugee Camp; Forced Migration; Information Need; Communication Behavior; Survey Study; Confirmatory Factor Analysis